Porang flour with and without soaking of keji beling extract increased ureum level on toxicity test - Ratna Dwi Astuti; Agus Prastowo; Veriani Aprilia (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2017)
Background: The porang tuber (Amorphophallus oncophyllus) is a functional food containing glucomannan that has many advantages in health. However, porang flour can not be consumed, because the high content of calcium oxalate that have the risk on kidney disease. It can be reduced by physical or chemical treatment. Keji beling (Strobilanthes crispa L. Blume) has been proved for its function in dissolving the calcium oxalate, but its uses in decreasing of calcium oxalate has not been studied yet.Objectives: To evaluate the effect of porang flour on ureum levels of wistar rat blood in acute toxicity test.Methods: The research was experimental with pre and post without control group design. The samples were 20 female Wistar rats, aged 8-10 weeks with body weight of 100-180 grams. Rats were divided into 4 groups of treatment those were native porang with the dose of 2000, 5000 mg/kg of body weight, porang flour with soaking of extract at the dose 2000 and 5000 mg/kg of body weight. Porang was incorporated orally into the mouth of rats after 18 hours of adaptation. At the 24th and  72nd hours after treatment, the bloods were collected and analyzed for their ureum levels.Results: The statistical test showed that there was an effect of porang flour with and without soaking of keji beling extract before and after treatment on ureum level at the dose of 2000 and 5000 mg/kg body weight, however there was no significant difference ureum level of the same dose at 24th or 72nd hours, except on the dose of 2000 mg / kg weight at the 72nd hour. Results of observation between the 24th hour compared to the 72nd hour showed that there was no significant difference of urea value (p> 0.05). Increased levels of ureum was influenced by the calcium oxalate content contained in porang flour. In TPM, ureum level was higher than that in TPK.Conclusions : The increase in urea levels was still in normal range, therefore porang flour is still safe for consumption.KEYWORDS: acute toxicity, porang flour, urea, keji beling